Experimental observation of low-frequency magnetohydrodynamic instabilities driven by energetic electrons in low hybrid current drive plasmas. (13th January 2021) - Yu, L.M.; Chen, W.; Shi, Z.B.; Wang, T.B.; Ding, X.T.; Ji, X.Q.; Ma, R.R.; Shi, P.W.; Bai, X.Y.; Li, J.X.; Yuan, B.S.; Li, Y.G.; et al.
Abstract: Energetic electrons driving low-frequency magnetohydrodynamic instabilities, e.g., electron fishbone (eFB) modes and electron beta-induced Alfvén eigenmodes (eBAEs), are found in co- and counter-current drive low hybrid current drive (LHCD) plasma in HL-2A, respectively. The eBAEs are found in LHCD plasma for the first time. Two branches eFB modes are observed in the core of plasma, and they can transit from the high-frequency one to the low-frequency one continuously. The different mode structures and positions are obtained by tomography of soft x-ray arrays. The frequency jump phenomena of eFB modes are also found. Two eBAEs, with poloidal and toroidal mode numbers m / n = 3/1 and 5/2, are found in the edge of the plasma. The single m / n = 3/1 mode is found when the LHCD power ( P LHCD ) is 0.44    MW. The strong m / n = 5/2 mode coexists with the weak 3/1 mode when P LHCD = 0.52   MW. Although the current drive direction of LHCD is opposite to the plasma current, the two eBAEs also propagate in the electron diamagnetic drift direction poloidally, which is the same direction as the eFB modes in co-current drive LHCD plasma. With increasing P LHCD (or changed current profile), the value of the edge safety factor ( q ) decreases. The evolutions of the mode numbers of eBAEs may be related to changes in the edge q factors.